2020
DOI: 10.1111/ejn.14885
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of H‐reflex responses and frequency‐dependent depression by repetitive spinal electromagnetic stimulation: From rats to humans and back to chronic spinal cord injured rats

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…We further observed a significant improvement in the FDD of the H-reflex following 5 Hz stimulation, indicating an increase in rate modulation of the plantar monosynaptic reflex pathway. While tSCS did not significantly improve FDD at 10 Hz stimulation compared to control SCI animals, the variability seen in the SCI group is common as rats often display a wide range of hyperreflexia after contusion injury (Petrosyan et al, 2020, see also Figure 4 ). The extent of variability in SCI animals may be a result of the extensive ability of rats to recover locomotion and functional capabilities after contusion SCI despite minimal white matter sparing (Magnuson et al, 2005; Scheff et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…We further observed a significant improvement in the FDD of the H-reflex following 5 Hz stimulation, indicating an increase in rate modulation of the plantar monosynaptic reflex pathway. While tSCS did not significantly improve FDD at 10 Hz stimulation compared to control SCI animals, the variability seen in the SCI group is common as rats often display a wide range of hyperreflexia after contusion injury (Petrosyan et al, 2020, see also Figure 4 ). The extent of variability in SCI animals may be a result of the extensive ability of rats to recover locomotion and functional capabilities after contusion SCI despite minimal white matter sparing (Magnuson et al, 2005; Scheff et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…They found that EMS (0.2 Hz for 35 min) on the spinal cord promotes transmission and facilitates NMDA receptor function including at motoneuron synaptic inputs from lateral white matter and corticospinal tract after hemisection SCI in rats without [ 34 ] or with exercise in combination [ 35 ]. It was also suggested that EMS not only modulates the lumbar motorneurons’ plasticity but also strengthens the neuro-muscular circuits and spinal networks after SCI in humans and rats [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism for restoration by EMF possibly also includes opioids besides NMDA receptors modulation [ 34 , 35 , 36 ], since EMF significantly relieves the pain of a wide variety via μ and δ opioid receptors [ 47 ] and increases the endogenous opioid and serotonin levels in the hypothalamus as well as serotonin in the brain stem [ 48 ]. Our study suggests that EMF stimulation attenuates hyperalgesia and allodynia in rats with complete thoracic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that one important function for sensory-motor cortex neurons projecting to the spinal cord is to regulate plastic adaptation of local spinal reflexes during ongoing posturo-locomotor activity. Indeed, phase-dependent depression of reflex loops was found to be reduced following incomplete SCI and able to recover, in a neurotrophic factor-dependent manner ( Côté et al, 2011 ), in response to spared corticospinal pathway stimulation ( Brus-Ramer et al, 2007 ; Petrosyan et al, 2020 ) or sensory-motor training ( Phadke et al, 2009 ; Côté et al, 2011 ). Corticospinal damage-induced spinal reorganization acutely leads to spinal hyperreflexia, which has been considered as maladaptive ( Tan et al, 2012 ), though such hyperreflexia may participate actively in the process of posturo-locomotor recovery by increasing the overall excitability of spinal networks below the lesion site (see below).…”
Section: Compensation After a Unilateral Lesion In Central Motor Circ...mentioning
confidence: 99%